A robust cumulative damage approach for the simulation of delamination under cyclic loading conditions. (1st February 2022) - Russo, Angela; Riccio, Aniello; Sellitto, Andrea
Abstract: Interlaminar damage evolution is one of the topics of main interest for composite materials research. An excellent level of knowledge has been achieved in the frame of the studies on delaminations propagation under static loading conditions (as a consequence of low velocity impacts). On the contrary, delaminations evolution under cyclic loading conditions is still an open challenge for the scientific community. Since expensive experimental campaigns are needed to assess the fatigue behaviour of Carbon Fibre Reinforced Polymers (CFRPs), the development and implementation of robust and efficient computational finite elements methodologies has become relevant. In this framework, a robust numerical finite element procedure able to simulate the fatigue driven delamination growth is proposed in this paper. A Paris-law based fatigue tool has been implemented in the commercial Finite Element Code ANSYS MECHANICAL via the Ansys Parametric Design Language (APDL) together with a static delamination procedure (named SMXB) previously developed by the authors. The proposed numerical procedure, based on the Virtual Crack Closure Technique (VCCT), is characterised by load step and element size insensitivity within non-linear incremental analyses. The proposed fatigue procedure, named FT-SMXB, has been preliminary validated at coupon level, by comparing the numerical results to literature experimental data on a unidirectional graphite/epoxy Double Cantilever Beam (DCB) specimen. Actually, the excellent agreement between the achieved numerical results and the literature experimental benchmark data proves the accuracy and the potential of the proposed methodology. Subsequently, a numerical application on a composite stiffened panel with skin stringer debonding under compressive-compressive fatigue loading conditions, has been performed. The Excellent agreement found between the obtained numerical results and available experimental literature data, for this application, in terms of number of cycles to failure and debonding propagation as a function of number of cycles, proves that the use of the proposed numerical tool can be extended, with profit, to geometrically complex and more realistic fatigue test cases.